Perencanaan Ulang Tempat Pengolahan Sampah Terpadu (TPST) Tambakrejo Kecamatan Waru Kabupaten Sidoarjo - Irfan Firmansyah; Mohamad Mirwan (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Volume of waste generation continues to increase in line with population growth, changes in quality and dynamics of community activities. The increasing waste generation will reduce space and disrupt human activities, thereby reducing the quality of human life due to the problem of waste generation. The more waste generation produced, the need for a better waste processing site, therefore it is necessary to carry out a Re-Planning of the Tambakrejo Integrated Waste Treatment Plant (TPST). In carrying out TPST planning, it is necessary to calculate the volume of waste generation, composition and so on. The calculation method used in this planning refers to SNI 19-3964-1994. This planning projects over the next 10 years. So it is projected that the highest waste generation reaches 14366.80 kg / day with a population of 20,524 people. The planned waste management and processing at TPST is divided into 2, namely organic waste is processed into compost and inorganic waste is sold to collectors, and for untreated residual waste is transported to landfill. The land area required in TPST planning is 1050 m2. The cost budget plan (RAB) that must be spent for planning TPST Tambakrejo is Rp. 1,864,842,051.